Influence of photobiomodulation on pain perception during initial orthodontic tooth movement - RUMÃO,Welinton Lemos (2020)
Abstract Introduction Laser in low intensity (LLI) has been used to reduce the discomfort and pain that is triggered by the forces applied during orthodontic treatment. Objective To evaluate the effect of LLI application in the pain perception of periodontal ligament initial compression, during orthodontic tooth movement; and to compare the effect of this therapy between men and women. Material and method The sample consisted of 30 volunteers, who needed orthodontic band placement on mandibular first molars. After insertion of the elastic separators, LLI was applied to the mesial and distal apical region (wavelength 808nm, energy 2J, time 20s and fluency of 8.32J/cm2) and at three points on the root region (wavelength 808nm, energy 1J, time 10s and fluency of 4.16J/cm2) of the first molar (irradiated side) and compared to the contralateral first molar (non-irradiated side), in three time intervals: 0hs, 24hs and 48hs. Pain perception was evaluated by the Visual Analog Scale (VAS), at 0hs, 24hs and 48hs after insertion, with significance of 5%. Result The pain level was observed to be significantly lower (p<0.05) on the irradiated side, irrespective of gender and time. Women presented a significantly higher pain level (p<0.05) than men, irrespective of time and side. There were no significant differences between the time intervals (p>0.05). Conclusion It was concluded that LLI reduced the perception of initial pain in patients in whom compression of the periodontal ligament was promoted by elastic separation, and that women had a greater perception of pain sensitivity in the time intervals studied.